Investigating the Maternal Factors Associated with Preschool Children’s Food Preferences; A Cross-Sectional Study: - Farajzadeh-Moghanjoughi, Nayyereh; Kheirouri, Sorayya; Alizadeh, Mohammad; Farsad-Naeimi, Alireza (Galen Medical Journal, 2019)
Background: Dietary patterns of children are determined by their food preferences, and mothers have important implications for these preferences. This study was aimed to investigate the maternal factors associated with children’s food preferences. Materials and Methods: In this cross-sectional study, a total of 576 healthy children aged 3-6 years participated from nursery schools through simple cluster sampling method and maternal factors associated with children’s food preferences were determined using a researcher designed, validated tool through face-to-face interview with mothers. Data were analyzed by SPSS software version 16 using General Linear Model to assess the correlations between different variables. Results: The children with diploma-educated mothers had fewer preferences in consuming nuts, vegetables, and fruits, and children with academic-educated mothers had fewer preferences in consuming nuts, beans, vegetables, fruits, drinks, condiments, and snacks (P<0.05). Children with employed mothers had fewer preferences for beans and drinks (P<0.02). Drinks preferences were lower among children whose mothers had good nutritional knowledge score (P<0.03). Proteins, beans, fruits, condiments, and snacks preferences were higher among children whose mothers had good nutritional attitude score (P<0.05). A positive correlation was found between the food preferences of children and mothers (0.377<B<0.570, P<0.001) in all food groups. Conclusion: The results of the study showed that mothers̓ educational level and their high nutritional knowledge and attitude could not guarantee the healthy dietary patterns of children. To promote children’s dietary patterns, it is imperative to improve the food preferences of mothers through specialized training. [GMJ.2019;8:e1652]